Group-Guidance Classes — An Anachronism? - Hymmen, Phyllis (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper attempts to answer the question raised in the title. It does so by briefly examining definitions, commentaries on groupguidance, and observations concerning research in the area. Passing mention is made of ongoing research on group-guidance classes by the author.